An Analysis of Slang Words Used for Comments on Instagram - Zaenul Wafa; Dwike Amalia Putri (Journalistics: Journal of English Teaching and Applied Linguistics, 2022)
The research entitled “An Analysis of Slang Words Used for Comments on Instagram”. aims to find slang words on Instagram and find out the meaning of these words. The researcher used descriptive qualitative method. Of the 25 slang words studied in this study, the researcher found slang forms which included 11 words in abbreviation, 1 word in shortened form and 13 words in interjection. Based on the results of the research, it shows that slang was thought of as vulgar and street language because it is only used by criminals and the lowest class of society. However, now slang is used by teenagers and certain social classes.